The Effect of The Covid-19 Pandemic On Self-Management Of Patients With Diabetes Mellitus Type 2: Literature Review - Risa Riyanti; Sutantri Sutantri (Universitas Aisyah Pringsewu, 2022)
During the COVID-19 pandemic, patients' mobility is severely restricted. They also adjust to the condition of their illness and have to think about the fear of contracting COVID-19. Diabetes mellitus is also one of the most common comorbidities found in COVID-19 patients. Therefore, it is necessary to know more about the influence or impact of the COVID-19 Pandemic on the self-management of patient with Type 2 Diabetes Mellitus. Melitus Type 2. This literature review uses 3 databases: Pubmed, Proquest, and Ebsco, which were published from 2019 to 2021 with the keywords